Cultural Themes in “English For Nusantara” Series of Textbook for Junior High School (Scripta : English Department Journal, 2026)
This study investigates the representation of cultural themes in the English for Nusantara textbook series for Indonesian junior high schools (Grades VII–IX). Using a qualitative descriptive design, the research applies content analysis based on Chen’s (2004) framework, which categorizes culture into big “C” (e.g., history, geography, politics, art, economy, traditions) and small “c” (e.g., daily routines, customs, food, values). The findings reveal a nearly balanced distribution between small “c” (51%) and big “C” (49%) cultural themes across the series. However, the emphasis varies by grade level. Grade VII predominantly features small “c” themes, especially food and daily routines, reflecting students’ everyday experiences. Grade VIII maintains a focus on small “c” culture while gradually introducing more big “C” elements such as literature and history. In contrast, Grade IX shows a clear shift toward big “C” themes, particularly geography and economy, indicating increased abstraction and global orientation. Overall, the series demonstrates a structured progression in cultural representation aligned with students’ cognitive and linguistic development.